A xylan assisted surface-enhanced Raman scattering substrate for rapid food safety detection - Xiang, Zhouyang; He, Mengyun; Li, Li; Bobokalonov, Jamshed; Dzhonmurodov, Abduvali; Ji, Xingxiang (Frontiers in Bioengineering and Biotechnology, 2022)
Cellulose fiber/paper-based surface-enhanced Raman scattering (SERS) is considered as a promising food safety detection technology due to its non-toxicity, low cost, flexibility, and hygroscopicity for possible rapid on-site agricultural product contaminant detection. However, it faces the problems of poor nobel metal adhesion and toxic noble metal reducing agent. In this study, a natural macromolecule—xylan was used as both a reducing agent and a stabilizing agent to prepare stable Au-Ag bimetal nanoparticles, which were anchored on the paper surface by xylans in order to fabricate an Au-Ag-FP SERS substrate. The results show that the SERS substrate has a high Raman enhancement performance and reproductively. The substrate can effectively detect trace pesticide, i.e. thiram, and the limit of detection is as low as 1×10-6 mol/L (0.24 ppm). In addition, the paper-based SERS substrate can be used for direct detection of pesticide residues on the surface of fruit. The Au-Ag-FP SERS substrate developed in this study has great potential in applications for rapid food safety detection.